Peer Feedback untuk Mengembangkan Kegiatan Menulis Bahasa Jepang di Kelas Menulis Bahasa Jepang (Sakubun) - Linna Meilia Rasiban; Ahmad Dahidi; Susi Widianti (Journal of Japanese Language Education and Linguistics, 2018)
The purpose of this study was to develop the quality of writing in middle-level Japanese language. From the results of the previousl questionnaires distributed, 80% of students found it difficult to develop story ideas into complete writing. The difficulty factor is influenced by the lack of time to develop ideas, beside that internal factors, namely mastery of vocabulary, mastery of sentence pattern structure. This study lasted for one semester at an university in Bandung, West Java, Indonesia with 20 students enrolled in  writing classes at  semesters 4. The students at the lower proficiency level reviewed peer texts. To examine gains in writing quality, a comparative analysis was conducted on writing samples collected at the beginning and the end of the semester. A questionnaire survey was also conducted to investigate the students’ perceptions t of assignments. The findings in this study that the students’ results needed to be feedback and evaluation to improve the ability to write Japanese short essays. Therefore, for further research  will need to apply peer feedback from peer tutors and evaluation from the teacher itself in order to improve writing skills  in writing quality.